A Comprehensive Review of Intelligent Home Automation Systems Using Embedded Devices and IoT - Tareq, Abdulla Al; Mostofa, Md Riad; Rana, Md Juel; Rahman, Md Sadiqur (Control Systems and Optimization Letters, 2024)
The integration of embedded devices and Internet of Things (IoT) technologies is the main subject of this thorough assessment, which examines the development and status of intelligent home automation systems. Intelligent home automation systems provide remote control and automation of household appliances and systems, with the goal of improving the comfort, safety, and energy efficiency of residential surroundings. The different designs and parts of home automation systems such as sensors, actuators, controllers, communication protocols, and user interfaces are examined in this overview. It draws attention to the function of embedded devices, which act as the essential building blocks of these systems by supplying the required connectivity and processing power. The evaluation also covers the use of IoT technologies, which enable smooth device interoperability and communication, opening the door to more advanced automation and control capabilities. Important developments in artificial intelligence, cloud computing, and machine learning that enhance these systems' intelligence and flexibility are also examined. The paper also discusses issues including security, privacy, standards, and user adoption and offers possible fixes as well as future research possibilities. Creating AI algorithms that will help home automation systems comprehend and react to user context and preferences more effectively which can be done soon. We hope that this review will give readers a thorough grasp of intelligent home automation systems and provide insights into their design.